2005
DOI: 10.1093/occmed/kqi177
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of prevalence and risk factors associated with playing-related musculoskeletal disorders in pianists

Abstract: Current evidence does not provide sufficient information regarding prevalence of and risk factors associated with PRMDs in pianists. Future studies should provide an operational definition of PRMD, use valid, reliable measurement tools, utilize a prospective cohort study design and perform appropriate statistical tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
93
0
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 31 publications
7
93
0
10
Order By: Relevance
“…Musculoskeletal pains have been reported in individuals with different occupations such as bus drivers, unskilled laborers, musicians, physical therapists, and computer keyboard operators [1][2][3][4][5][6][7] . Recently, ergonomic mechanisms related to the development of work-related musculoskeletal disorders (MSD) have drawn substantial interest [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal pains have been reported in individuals with different occupations such as bus drivers, unskilled laborers, musicians, physical therapists, and computer keyboard operators [1][2][3][4][5][6][7] . Recently, ergonomic mechanisms related to the development of work-related musculoskeletal disorders (MSD) have drawn substantial interest [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Performance related musculoskeletal disorders (PRMDs) are highly prevalent in professional musicians (1)(2)(3)(4)(5)(6) and professional orchestral musicians particularly, endure significant performance-related pain (7). A systematic review of pain prevalence in instrumentalist musicians found a lifetime prevalence rate of up to 85% (7).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has investigated the play-related musculoskeletal disorder and Upper Limb Pain among musician such as pianists, guitarists, violin, and string players 4,6 . However, to our knowledge there have not been enough studies to investigate the rate of musculoskeletal disorder or Upper Limb Pain among Veena players.…”
Section: Introductionmentioning
confidence: 99%
“…Repetitive strain injury and overuse syndrome were reported among pianists, guitarists and string players which lead to pain, weakness, lack of control, tingling and numbness 6 . In addition, Steinmetzet al (2102) stated that pain and overuse syndromes are shared problems among musician; 80% of professional musician involved with pain in their musculoskeletal system.…”
mentioning
confidence: 99%